COLLOIDAL, TRIBOLOGICAL AND SENSORY PROPERTIES OF ORAL NUTRITIONAL SUPPLEMENTS - BOT, F.; CROWLEY, S.V.; O’SULLIVAN, J.J.; O’SULLIVAN, M.G.; O’MAHONY, J.A. (Italian Journal of Food Science, 2020)
This study aims to evaluate the physicochemical and sensory properties of oral nutritional supplements (ONSs). High physical stability was measured in ONSs with mean particle sizes <0.33 um and viscosity >19.3 mPa·s. ONSs formulated with dairy-soy protein mixtures displayed low friction coefficients, whereas ONSs containing dairy proteins alone had high friction coefficient values in the boundary regime. Sensory analysis revealed low to medium liking across the products and the highest preference was found in samples with the highest perceived ‘sweetness’, ‘vanilla aroma’ and ‘thickness’. The results will underpin the formulation of novel ONSs with good physical stability and sensory acceptability.